Unionist vs. Nationalist: Potential Re-emergence of Identity Crisis in Post-Brexit Northern Ireland - Andy Fernanda Probotrianto Probotrianto (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2020)
As the world begin to enter another decade of the third millennia, Europe has been struck with various challenges that greatly affects its surrounding geopolitics that, depend on the path further taken, would decide its future: whether maintaining solidarity and regional ‘fraternity’, typically in context of European Union (EU), or towards complete jeopardy and dissolution of the long-lasting union that has been tighten since the end of the Second World War. However, preference of member-states is beginning to drift away to the latter as crisis and problems continue to spring, both internally, such as cases with Greek’s monetary inflation, and externally, concerning massive influx of refugees coming from the Middle East and Africa. As suggested by constructivism, the key of successful resolution depends on the intensity of diplomatic communication. By doing so, both countries should have deep understanding of each other’s perspective. In addition, views and interest of Unionist and Nationalist side should be taken into account for in mitigating possible rise of new conflict.